A Struggle For A Better Life Reflected In Paulo Coelho's Eleven Minutes Novel (2003): An Individual Psychological Approach - Astuti, Ika Puji; , Drs. Abdillah Nugroho, M. Hum; , Siti Fatimah, S. Pd, M. Hum (2014)
The major problem of this study is how Maria struggle to be better life reflected in Eleven Minutes Novel. The objective of this study is to analyze the novel based on its structural elements and to analyze the novel based on individual psychological approach as major theory and strive for success as issue. In analyzing Eleven Minutes Novel the researcher uses qualitative method and individual psychological approach. The data sources consist of primary data and secondary data sources. The primary data source is the novel Eleven Minutes itself and the secondary data sources are the other sources related to the analysis of the object and issue. The method of the data collection is descriptive analysis. The first result of the study in structural analysis shows that Eleven Minutes Novel is simple fiction based on portion for structural elements. The second result in personality analysis, Maria who leaves her Brazilian home to go to Geneva, Switzerland, in hopes of great adventure and great love. Her situation does not prove to be what she had hoped, and she pursues a career in prostitution in order to make money quickly to return home. During her time in Switzerland, Maria experiences pain, pleasure, and love, and must decide the correct path for her life.